Perancangan Website Informasi Dinas Perumahan, Kawasan Permukiman dan Pertanahan Provinsi Bengkulu - Yunika, Astri; Harianto, Ozi; Idaman, Dewa; Ardiansyah , Ardiansyah; Darmi, Yulia (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
The increasing use of digital technology has encouraged government agencies to provide public services online. In this context, creating a website for the Department of Housing, Settlement Areas and Land (Perkim) is important to facilitate access to information and services related to housing, settlements and land for the community. This article aims to explain the process of creating a Perkim Service website and strategies that can be used to optimize digital public services.First, we discuss the importance of the Perkim Department website as a means of increasing transparency, accessibility and efficiency in the provision of information and services to the public. Next, we discuss the technical steps in creating a website, including platform selection, intuitive user interface design, and integration of important features such as property search, online registration, and problem reporting. In addition, we highlight the importance of information security and data privacy in the development of the Department of Perkim website.Next, this article explores strategies to increase public adoption and use of the Dinas Perkim website, including outreach campaigns, user training, and user feedback. We also discuss the importance of regular website maintenance and updates to maintain the quality of the services provided.Through this discussion, it is hoped that readers will gain a better understanding of the importance of creating a Perkim Service website and strategies for optimizing digital public services in the housing, settlement and land sectors.